Cognitive Epileptiform Disintegration in Children - Gamirova, R; Gorobets, E; Marulina, V (KnE Life Sciences, 2018)
Cognitive epileptiform disintegration is a specific disease associated with severe epileptiform activity on the EEG in the absence of epileptic seizures accompanied by different developmental cognitive disorders in children. The quantitative and qualitative characteristics of these developmental disorders have changed in the last 10 years. The article presents the analysis of cognitive epileptiform disintegration specificity and the results of the survey that included 57 children aged 2–7 with developmental disorders caused by epileptiform activity that was revealed during video EEG monitoring with sleep deprivation. The children were assessed with 19-channel EEG, synchronized with a video-monitoring system. Recording time was 1–2 hours. The psychometric methods used for the assessment of cognitive functions were three batteries of tests for children according to their age (2 years – MacArthur Communicative Development Inventories, 3–5 years – subtests created in Kazan’ Federal University, 6–7 years – T.V. Akhutina’s methods of neuropsychological diagnosis). The results of the research show that cognitive impairment in children with cognitive epileptiform disintegration aged 2–7 are complex, and predominantly they are the results of general developmental disorders associated with constant strong electrical impact on the functional blocks of the brain. Speech is most severely affected, both expressive and impressive, but speech disorders are always accompanied by the deficit of visual-spatial and kinesthetic analyzers, the deficit of the third functional block development and behavioral (predominantly autism-like) disorders. Keywords: cognitive epileptiform disintegration, developmental disorders, speech disorders, video EEG monitoring, higher cortical functions, assessment of speech, assessment of cognitive functions